Creating positive synergies between risk management and transfer to accelerate food system climate resilience - Shahbaz Mushtaq; Jarrod Kath; Roger Stone; Ross Henry; Peter Läderach; Kathryn Reardon-Smith; David Cobon; Torben Marcussen; Neil Cliffe; Paul Kristiansen; Frederik Pischke (Climatic Change, 2020)

A participatory systems approach to understanding climate adaptation needs - Helen Ross; Sylvie Shaw; David Rissik; Neil Cliffe; Susie Chapman; Vanessa Hounsell; James Udy; Nghia Trong Trinh; Jess Schoeman (Climatic Change, 2015)
Emerging literature on climate adaptation suggests the need for effective ways of engaging or activating communities and supporting community roles, coupled with whole-of-system approaches to understanding climate change and adaptation needs. We have developed and evaluated a participatory approach to elicit community and stakeholder understanding of climate change adaptation needs, and connect diverse community members and local office bearers towards potential action. The approach was trialed in a series of connected social-ecological systems along a transect from a rural area to the coast and islands of ecologically sensitive Moreton Bay in Queensland, Australia. We conducted ‘climate roundtables’ in each of three areas along the transect, then a fourth roundtable reviewed and extended the results to the region as a whole. Influence diagrams produced through the process show how each climate variable forecast to affect this region (heat, storm, flood, sea-level rise, fire, drought) affects the natural environment, infrastructure, economic and social behaviour patterns, and psychosocial responses, and how sets of people, species and ecosystems are affected, and act, differentially. The participatory process proved effective as a way of building local empathy, a local knowledge base and empowering participants to join towards future climate adaptation action. Key principles are highlighted to assist in adapting the process for use elsewhere.